The Influence of Brand Image, Product Quality and Price on Samsung Smartphone Product Purchase Decisions (Case Study on Employees of PT Angkasa Pura Aviasi Kualanamu International Airport) - Akhmad Syarif Sinaga; Arlina Nurbaity Lubis; Beby Karina Fawzeea Sembiring (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
Brand image, product quality and price get a positive impression from the majority of respondents and get a significance value of 0.000, 0.001 and 0.000 respectively. From the brand image variable, it can be seen that the majority of respondents agree that Samsung smartphones have a good reputation and are innovative, thereby increasing employee confidence. The product quality variable states that Samsung smartphones are considered to have good performance and are attractive and in accordance with what is needed by employees. The price variable states that Samsung smartphones have affordable prices and are in accordance with the quality of the products needed by employees. The purpose of this study is to find out and analyze whether brand image, product quality and price have an influence on purchasing decisions for Samsung smartphone products. The respondents used were employees from PT Angkasa Pura Aviasi Kualanamu International Airport. This study uses a quantitative approach and uses multiple linear regression analysis. The total population at PT Angkasa Putra Aviasi Kualanamu International Airport is 544 employees. Where the population in this research are employees at PT Angkasa Pura Aviasi Kualanamu International Airport who have used Samsung smartphones whose number is not identified so that the sample used in this study was 108 employees in the company. The results of this study indicate that brand image, product quality and price have a positive and significant influence on purchasing decisions for Samsung smartphone products.